2015
DOI: 10.1016/j.physletb.2015.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Two-loop QCD corrections toBcmeson leptonic decays

Abstract: The two-loop quantum chromodynamics (QCD) radiative corrections to the B c meson leptonic decay rate are calculated in the framework of the non-relativistic QCD (NRQCD) factorization formalism. Two types of master integrals appearing in the calculation are obtained analytically for the first time. We calculate the short-distance coefficient of the leading matrix element to order α 2 s by matching the full perturbative QCD calculation results to the corresponding NRQCD results. The result presented in this work… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…[13] and [14] respectively, and a few years ago even the NNNLO result for Υ → e + e − process was obtained [15]. In recent years, at the NNLO level many calculations are performed for quarkonium production and decays [16][17][18]. It is interesting to note that in recently, the NNLO corrections to γγ * → η c (η b ) transition form factor and η c (η b ) → light hardrons were calculated numerically [19,20].…”
Section: Jhep01(2018)091mentioning
confidence: 99%
“…[13] and [14] respectively, and a few years ago even the NNNLO result for Υ → e + e − process was obtained [15]. In recent years, at the NNLO level many calculations are performed for quarkonium production and decays [16][17][18]. It is interesting to note that in recently, the NNLO corrections to γγ * → η c (η b ) transition form factor and η c (η b ) → light hardrons were calculated numerically [19,20].…”
Section: Jhep01(2018)091mentioning
confidence: 99%
“…For the B c meson, the decay constant can in principle be determined by leptonic and radiative-leptonic decays [56][57][58][59], both of which show lack of experimental data yet. Twoloop contributions in the NRQCD framework have been calculated in Ref.…”
Section: Input Parametersmentioning
confidence: 99%
“…Twoloop contributions in the NRQCD framework have been calculated in Ref. [58] and the authors have found…”
Section: Input Parametersmentioning
confidence: 99%
“…To date, perturbative calculations beyond NLO have been conducted only for a few exclusive processes involving quarkonium, exemplified by O(α 2 s ) corrections to Υ(J/ψ) → e + e − [11,12] (Notice the O(α 3 s ) coefficients were also available recently [13,14]), η b,c → γγ [15,16], χ c0,2 → γγ [17], and B c → ℓν [18,19], as well as the O(α 2 s ) correction to the γγ * → η c,b transition form factor [16]. Only two-loop virtual corrections are required in calculating these hard matching coefficients, since they correspond to exclusive quarkonium decays or productions.…”
mentioning
confidence: 99%